2007
DOI: 10.1021/cg700825v
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Vertically Aligned ZnO Rods with a Multistage Terrace Structure and Their Improved Solar Cell Efficiency

Abstract: This work reports a solution-based approach to grow high-density vertically aligned ZnO rod arrays with a multistage terrace structure (HDVAMT) on Au nanoparticle covered glass substrates. The solar cell performance of HDVAMT is 10 times better than that of the disordered ZnO due to the much higher short circuit current (J sc ). This significant improvement of J sc is attributed to two factors: the vertically aligned structure, which provides smoother electron transport channels, and the high density of the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 16 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…For example, one study found that a ZnO nanorod array led to a ten-fold increase in the photovoltaic efficiency when compared to a randomly oriented nanorod film. [119] However, the insufficient surface area of nanowire/ nanorod arrays seems to be the primary factor that limits the amount of dye adsorption as well as the conversion efficiency of the cells. Many attempts have been made to solve this problem.…”
Section: à3mentioning
confidence: 99%
“…For example, one study found that a ZnO nanorod array led to a ten-fold increase in the photovoltaic efficiency when compared to a randomly oriented nanorod film. [119] However, the insufficient surface area of nanowire/ nanorod arrays seems to be the primary factor that limits the amount of dye adsorption as well as the conversion efficiency of the cells. Many attempts have been made to solve this problem.…”
Section: à3mentioning
confidence: 99%
“…During the past few years, nanocrystals of zinc oxide have attracted a lot of interest due to their potential applications, such as solar cells [1][2][3], photocatalysts [4,5], luminescent materials [6,7], gas sensors [8][9][10] and so on. Different technologies have been developed to synthesize ZnO nanocrystals with different shapes and sizes, including hydrothermal synthesis [11,12], sol-gel method [13][14][15], thermal decomposition [16,17], microwave irradiation method [18][19][20], chemical vapor deposition [21,22], and continuous flow techniques [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in nanoscale structures can be attributed to their unique optical and electrical properties due to quantum confinement effects and high surface-to-volume ratios, with great prospect of applying them as building blocks in electronic and photonic devices [2][3][4][5]. The methods reported for the synthesis of semiconducting oxide nanowires include chemical bath deposition [5][6][7][8], hydrothermal synthesis [9][10][11][12][13], chemical vapor deposition [14,15], thermal evaporation [16,17] and sputtering [18,19]. Hydrothermal synthesis is often used because it allows control of size, morphology and crystallinity by tuning of the experimental variables.…”
Section: Introductionmentioning
confidence: 99%